O PROCESSO DE MORTE E MORRER: CONSIDERAÇOES DE ACADÊMICOS DE ENFERMAGEM EM UMA UTI - Spengler, Rúbia O.; Mastella, Rosane C. G.; Stumm, Eniva M. F.; Abreu, Paola B. d.; Sandri, Andréla; Althaus, Juciele C.; Fontana, Itiana V.; Roncato, Claudia A. (Salão do Conhecimento, 2013)
Resumo